2023
DOI: 10.3390/cancers15041095
|View full text |Cite
|
Sign up to set email alerts
|

Lithium in Cancer Therapy: Friend or Foe?

Abstract: Lithium, a trace element important for fetal health and development, is considered a metal drug with a well-established clinical regime, economical production process, and a mature storage system. Several studies have shown that lithium affects tumor development by regulating inositol monophosphate (IMPase) and glycogen synthase kinase-3 (GSK-3). Lithium can also promote proliferation and programmed cell death (PCD) in tumor cells through a number of new targets, such as the nuclear receptor NR4A1 and Hedgehog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 154 publications
0
4
0
Order By: Relevance
“…In addition to the current use of lithium in the therapy of bipolar disorders, lithium is also being investigated as a drug for experimental cancer therapy. It was found that lithium has the various antitumor effects in cancer models in vitro and in vivo (Villegas‐Vázquez et al, 2023; Yang et al, 2023); however, the data regarding lithium accumulation in tumors are limited. Previously, we have revealed that lithium carbonate accumulates in the tumor at a concentration higher than 20 μg/g in B16 mouse melanoma model in vivo (Taskaeva et al, 2023); nevertheless, it is not clear whether accumulation is the same for different melanoma cell lines or other cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the current use of lithium in the therapy of bipolar disorders, lithium is also being investigated as a drug for experimental cancer therapy. It was found that lithium has the various antitumor effects in cancer models in vitro and in vivo (Villegas‐Vázquez et al, 2023; Yang et al, 2023); however, the data regarding lithium accumulation in tumors are limited. Previously, we have revealed that lithium carbonate accumulates in the tumor at a concentration higher than 20 μg/g in B16 mouse melanoma model in vivo (Taskaeva et al, 2023); nevertheless, it is not clear whether accumulation is the same for different melanoma cell lines or other cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ginsenoside Rb1 promotes autophagy in colon cancer cells through the generation of reactive oxygen species and activation of the JNK signaling pathway (Kim 2013 ). Lithium induces autophagy along with autophagosomes and autophagic lysosomes in several cancers, including melanoma, hepatocellular carcinoma, cervical carcinoma, and renal carcinoma (Yang et al 2023 ). Lithium agents such as lithium acetoacetate (LiAcAc), lithium chloride (LiCl), lithium citrate (Li 3 C 6 H 5 O 7 ) and lithium carbonate (Li 2 CO 3 ) can be used to induce autophagy and thus inhibit tumor growth (Villegas-Vázquez et al 2023 ).…”
Section: Application Of Autophagy Inducersmentioning
confidence: 99%
“…Lithium inhibits IMPase to induce mTOR-independent autophagy. Simultaneously, it inhibits GSK-3β, which, in turn, reduces autophagy by activating mTOR 33 , 34 . The differential effects of lithium on autophagy may be attributed to varying therapeutic concentrations 35 .…”
Section: Molecular Mechanismmentioning
confidence: 99%